Query on predicate logic


#1

Given that B(x) means “x is a bat”, F(x) means “x is a fly”, and
Given that
B(x) means “x is a bat”,
F(x) means “x is a fly”, and
E(x, y) means “x eats y”,
what is the best English translation of ∀x(F(x) → ∀y(E(y, x) → B(y)))?

(A) all flies eat bats
(B) only bats eat flies
© every fly is eaten by some bat
(D) every bat eats flies


#2

C) Every fly is eaten by some bat.
Because if we directly convert the language, it says " All x that is a fly implying all y that eats x implies y is a bat".